PREPARATION AND EVALUATION O/W CREAM FOR SKIN PSORIASIS - PURUSHOTHAM RAO K; KHALIQ K; KHARAT S S; SAGARE P; PATIL SK (International Journal of Pharma and Bio Sciences, 2010)
Skin psoriasis which is a common chronic inflammatory dermatosis affecting 1% to 2% of people in the general. Keratolytic agents are helpful in reducing scale and hyperkeratosis by causing softening and desquamation of the stratum corneum and most beneficial in extremely thick or scaly psoriatic plaques. In the present study Salicylic acid chosen as model drug which is the most effective keratolytic agent. In present work o/w emulsion based cream formulation contain suitable combination of oil phase and aqueous phase along with preservatives, prepared and subjected to various physiochemical parameters like drug content, pH, spread ability, tube extrude ability, viscosity and IR studies. In-vitro drug release was carried out in phosphate buffer (pH 7.4) and compared with marketed formulation. Stability studies of selected formulation were also done at ambient temperature (30o C & 40o C) for the period of six months as per ICH guidelines. The selected formulation were subjected for primary skin irritation test in rabbits, guinea pigs, and healthy human volunteers for 72 hours and observed for any skin rashes, inflammation, itching, or redness on applied portions. Drug content, pH, Spread ability, Tube extrude ability of the formulation was found to be 95.00%, 6.1, 11.32gm.cm/sec, 94.96% respectively. From rheogram it is concluded that formulation shows pseudo plastic flow property.